2020
DOI: 10.1182/blood.2020006964
|View full text |Cite
|
Sign up to set email alerts
|

Use of convalescent plasma in hospitalized patients with COVID-19: case series

Abstract: Two case series examining the impact of convalescent plasma on patients with COVID-19 suggest some clinical benefit from early administration and modest impact on parameters of inflammation. Further assessment of the impact of this intervention awaits controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
157
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(169 citation statements)
references
References 22 publications
(33 reference statements)
10
157
2
Order By: Relevance
“…As mentioned above, neutralizing antibodies are protective as demonstrated in different animal models [ [39] , [40] , [41] , [42] , [43] ]. Accordingly, the administration of convalescent plasma to COVID19+ individuals improve their clinic status, at least in those treated with High neutralizing plasma during early disease stages [ [49] , [50] , [51] , [52] ]. Actually, no clinical benefit was observed in those patients requiring invasive mechanical ventilation [ 50 ].…”
Section: Role Of Antibodies In Pathogenesis and Protectionmentioning
confidence: 99%
“…As mentioned above, neutralizing antibodies are protective as demonstrated in different animal models [ [39] , [40] , [41] , [42] , [43] ]. Accordingly, the administration of convalescent plasma to COVID19+ individuals improve their clinic status, at least in those treated with High neutralizing plasma during early disease stages [ [49] , [50] , [51] , [52] ]. Actually, no clinical benefit was observed in those patients requiring invasive mechanical ventilation [ 50 ].…”
Section: Role Of Antibodies In Pathogenesis and Protectionmentioning
confidence: 99%
“…Among the ve studies included in the current metaanalysis, two studies suggested that convalescent plasma treatment appeared effective and safe for COVID-19 cases [1,2]. In addition, Hegerova et al reported that convalescent plasma use in severe and critically ill patients with COVID-19 may improve survival if given early in the course of disease [5]. Zeng et al observed that convalescent plasma transfusion could discontinue SARS-CoV-2 shedding and contributed to longer survival in COVID-19 patients with respiratory failure, although it could not reduce mortality in critical end-stage COVID-19 patients [2].…”
Section: Although Convalescent Plasma Therapy Has Been Thoroughly Evamentioning
confidence: 90%
“…However, a curative treatment or effective speci c vaccine againstSARS-CoV-2 infection is unavailable. Recently, several studies have been performed to evaluate the effects of COVID-19 convalescent plasma transfusion on the clinical outcomes in patients with severe/critical COVID-19 [1][2][3][4][5]. However, the results from these studies aredatable, and thus its useremains investigational.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…What other evidence underpinned the FDA’s controversial decision? The most recent version of the Cochrane living systematic review on convalescent plasma9 was available, along with more recent randomised and non-randomised studies 4101112131415. However, the only two randomised trials (189 participants in total)34 could not be combined in meta-analyses because they used different times for assessing mortality and different rating scales for clinical outcomes.…”
mentioning
confidence: 99%